A model for prognosis of development of left ventricular systolic dysfunction in patients with acute myocardial infarction and type 2 diabetes mellitus taking into account tenascin C level - M. Yu. Koteliukh (Zaporožskij Medicinskij Žurnal)
The aim of the study was to elaborate a model for prediction of development of left ventricular systolic dysfunction in patients with acute myocardial infarction (AMI) and type 2 diabetes mellitus taking into account tenascin C level and estimation of predictive value of this indicator in AMI.